PERAN ORANG TUA DALAM PENANAMAN KARAKTER CINTA LINGKUNGAN PADA ANAK USIA DINI DI DESA ARANG LIMBUNG KABUPATEN KUBU RAYA - Feronika Feronika; Marmawi R; Dian Miranda (Universitas Tanjungpura, 2021)
AbstractThis research aimed to describe the role of parents in the cultivation of character of love for the environment in early childhood in arang limbung village, kubu raya district. The method use in this research was the descriptive method with the qualitative design. The subject of this research was parents and early childhood at RT 008/ RW 008 arang limbung village kubu raya district. The instrument used to gather the data in this research were participant observation, interview, and documentation. The result showed: 1. The role of parents as an educator in planting the character of love for the environment in children, parents always teach children to love the environment yait by not littering, gardening, love plants, wash hands with soap before and after eating and shower use soap, 2. The role of parents as a mentor in planting character love the environment in children, parents always supervising and guiding every child’s activity inside and outside the house so that children get used to love the environment. Thus the role that parents have applied to planting environmental love character in early childhood in arang limbung village kubu raya district has been implemented properly.Keywords: Role of Parents, Environmental Love Character